If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f(-2)=4(-2)+10
We move all terms to the left:
f(-2)-(4(-2)+10)=0
We add all the numbers together, and all the variables
f(-2)-2=0
We multiply parentheses
-2f-2=0
We move all terms containing f to the left, all other terms to the right
-2f=2
f=2/-2
f=-1
| 3/5=7/kk= | | 3(3y−7)=2y+7 | | 3^(x+2)=9^(x+1) | | 10/4=35/x | | X=2x-4x | | 7n+5(n+2)=10n+20 | | z−9=6 | | 14=-6+w | | 12x+5(14x-14)= | | -18+r=-25 | | -7u-7/4=3/4u-7/3 | | -4+b=-5+6b | | -25=f-18 | | a-7=23-2a | | x+27=30+89x | | 6+f=71-f | | 7(l−5)=21 | | 7p+8p-12=36 | | s-2=-6+3s | | -9+n=13-5n | | 7i−4=66 | | 3x-18=7x-44 | | 14+m=24-12+3m | | 2/5=3/z-2 | | 12u-7u=40 | | t12-11=-9 | | 11w=54+5w | | 29=38=x | | 12t −11=−9 | | (y-6.5)/3=-2 | | 4/14=18/x | | 2t1=5 |